Dimensional changes of acrylic resin denture bases: conventional versus injection-molding technique. - Jafar Gharechahi; Nafiseh Asadzadeh; Foad Shahabian; Maryam Gharechahi (Tehran University of Medical Sciences, 2014)
Acrylic resin denture bases undergo dimensional changes during polymerization. Injection molding techniques are reported to reduce these changes and thereby improve physical properties of denture bases. The aim of this study was to compare dimensional changes of specimens processed by conventional and injection-molding techniques.SR-Ivocap Triplex Hot resin was used for conventional pressure-packed and SR-Ivocap High Impact was used for injection-molding techniques. After processing, all the specimens were stored in distilled water at room temperature until measured. For dimensional accuracy evaluation, measurements were recorded at 24-hour, 48-hour and 12-day intervals using a digital caliper with an accuracy of 0.01 mm. Statistical analysis was carried out by SPSS (SPSS Inc., Chicago, IL, USA) using t-test and repeated-measures ANOVA. Statistical significance was defined at P